(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
The environment is increasing emerging as a critical component of the socio-economic development of average Nigerians as it has not only been valuable to traditional societies for their nutritional and health needs, but also, crucial to the realization of fundamental rights. This is more pertinent as it relates to the inhabitants of the Niger Delta region of Nigeria where the activities of oil multinational companies has made the region to be synonymous with oil pollution, devastated environment and human right abuses. Unsurprisingly, Nigerian courts are increasingly being called upon to adjudicate on issues relating to pollution and other environmental abuses by both private and public persons within the oil sector. Most times, environmental disputes are brought to the court in Nigeria as tortuous cases seeking compensation for damages. Remedies can also be sought under statutory laws or as writ petitions under the fundamental human right enforcement procedure rules. The latter implicates the provision of a human right to healthy environment under statutory laws, and whether such right is recognised as binding by the courts in Nigeria. This paper explores how environmentalism can be triggered in Nigeria through the judicial recognition of the right to a satisfactory environment. It recognises that there are some efforts towards such judicial recognition of the right. However, it argues that to promote environmentalism in Nigeria, there is a need to deepen judicial recognition of the right by detailed pronouncements on the justiciability of the right.